Producción de una crema hidratante rica en B-carotenos obtenidos a partir de la Levadura Saccharomyces Cerevisiae (2021)
B-carotene is a pigment that plays a significant role in today's cosmetics industry. It is generally extracted from fruits, vegetables, bacteria, etc. Its main characteristics include its coloring and antioxidant properties as a precursor of vitamin A, thus protecting the skin and strengthening the immune system. However, in the industry, its use from natural origins is still under investigation. The purpose of this work was to design a W/O emulsion fortified with B-carotene for topical use, thus creating 4 samples varying the dispersed phase concentration and the presence of stabilizer. Carotenoid was obtained from a Saccharomyces cerevisiae yeast strain from the ultrasound sonication method with the solvent Ethanol. Stability tests were performed: destabilization index, particle size and centrifugation; characterization: organoleptic properties, pH, viscosity and antioxidant power under a DPPH test. It was then found that the extracted B-carotene possesses a concentration of 1.75 mg/ml. It was determined that the best cream formulation was at 80% aqueous phase with addition of stabilizer taking into account its stability, structure and organoleptic properties. Finally, it was concluded that the cream must maintain a concentration of B-carotene greater than 4.6 mg/ml for its antioxidant activity to exceed 95%.